Red- and NIR-emitting lanthanide complexes for photo- and electroluminescent nanothermometry in the cryogenic and high-temperature range - Fedichkina, Anna D.; Koshelev, Daniil S.; Vashchenko, Andrey A.; Goloveshkin, Alexander S.; Latipov, Egor V.; Burlov, Anatolii S.; Dmitriev, Artem V.; Chernyadyev, Andrey Yu; Lypenko, Dmitry A.; Utochnikova, Valentina V. (Optical materials, 2024)
Ratiometric luminescent thermometers, particularly lanthanide-based, become very important, and long wavelength range is of particular interest due to low signal scattering. With this in mind, a series of new red and NIR emitting lanthanide Schiff base complexes were synthesized and characterized in detail for use as components of luminescent thermometers. Red-emitting europium complexes demonstrated high temperature sensitivity (up to 7 %/K) in the cryogenic temperature range (80–200 K), where the ligand-to-europium luminescence intensity ratio (LIR) was used as a signal. In contrast, NIR emitting ytterbium complexes demonstrated no sensitivity in the cryogenic range; however, their luminescence was sensitive to high temperatures (300–600 K), which is currently of particular interest. Ytterbium and europium complexes were also tested in OLEDs, and due to high temperature sensitivity, europium complexes were used for the first electroluminescent thermometers. •High sensitivity of red emitting europium complexes in the cryogenic temperature range (80–200 K) obtained.•High sensitivity of NIR emitting complexes towards the high temperatures (300–600 K) obtained.•The first electroluminescent thermometry based on europium complexes obtained.